2015
DOI: 10.1016/j.sab.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of particle size distributions produced during ultra-violet nanosecond laser ablation and their relative contributions to ion densities in the inductively coupled plasma

Abstract: Relative contributions to ion densities in the inductively coupled plasma (ICP) of particles of various sizes produced by laser ablation (LA) were investigated. Particles generated by 266 nm, ns LA of BaF 2 , CaF 2 , and a scandium aluminum alloy, characterized using SEM, consisted of hard and soft agglomerates, spherical particles, and irregularly-shaped particles. Although soft agglomerates and spherical particles were common to aerosols generated by LA in all cases, hard agglomerates appeared to be unique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…However, their spacing is at least by one order of magnitude greater than in the case of XUV-CDL irradiation and they often cross each other at certain angles while the lines of the XUV-LIPSS reported here are dominantly parallel. Even nanoparticles emitted from BaF2 irradiated by the nanosecond laser radiation often show a calcite crystal habitus and sharp edges [32]. This all indicates that laser-induced cleavage of alkali-earth halide crystals along the crystallographic planes can be observed in both the cases but with the long-wavelength laser radiation they have not been found to be as regular and uniform as observed on the XUV-CDL-illuminated surfaces in the present study.…”
Section: Discussion and Outlookcontrasting
confidence: 43%
See 1 more Smart Citation
“…However, their spacing is at least by one order of magnitude greater than in the case of XUV-CDL irradiation and they often cross each other at certain angles while the lines of the XUV-LIPSS reported here are dominantly parallel. Even nanoparticles emitted from BaF2 irradiated by the nanosecond laser radiation often show a calcite crystal habitus and sharp edges [32]. This all indicates that laser-induced cleavage of alkali-earth halide crystals along the crystallographic planes can be observed in both the cases but with the long-wavelength laser radiation they have not been found to be as regular and uniform as observed on the XUV-CDL-illuminated surfaces in the present study.…”
Section: Discussion and Outlookcontrasting
confidence: 43%
“…It is clearly visible that the periodic nanostructures observed in the XUV-CDL irradiation experiment differ from the morphology of all the damage patterns observed on alkali-earth-halide surfaces exposed to radiation of various kinds in numerous studies reported earlier [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. We should keep in mind that an attenuation length of 46.9-nm XUV-CDL radiation in BaF 2 is very short, i.e., only about 10 nm [40,41].…”
Section: Discussion and Outlookmentioning
confidence: 90%